Characterization of brazilian accessions of wild arachis species of section arachis (fabaceae) using heterochromatin detection and fluorescence in situ hybridization (FISH) - Custodio, Adriana Regina (2013)
Fil: Custodio, Adriana Regina. Universidade Federal de Santa Catarina. Centro de Ciências Agrárias. Programa de Pós-Graduação em Recursos Genéticos Vegetais; Brasil.